VARIABILITAS TEKANAN DARAH INTRADIALISIS PASIEN PENYAKIT GINJAL KRONIS DENGAN HEMODIALISIS BERKELANJUTAN - Maulana Muhtadin Suryansyah; Mochammad Thaha; Budiono Budiono (Universitas Airlangga, Surabaya, Indonesia, 2019)
Background: Various of studies report there was a link between changes in blood pressure during hemodialysis and the level of patient’s morbidity and mortality. Higher amount of mortality was found in groups of patients who have lower or higher blood pressure. Thus it is important to know the variability of blood pressure during hemodialysis. Objective: This study aims to determine blood pressure variability, namely systolic blood pressure and diastolic blood pressure during hemodialysis and determine the significance of changes in every hour of measurement. Material and method: The design of this study used a cross-sectional method with a total sample of 15 patients who have been diagnosed with Chronic Kidney Disease (CKD) and have been ungergone hemodialysis stably in the last 3 months. The data obtained were processed using paired T-Test and Wilcoxon test. Result: There was no significant difference in systolic blood pressure between hourly systolic blood pressure and a tendency to increase the mean systolic blood pressure during hemodialysis. In diastolic blood pressure, there was a difference between the mean diastole 3 and diastole 4, p = 0.007 (<0.05), while in other observation there were no significant differences. In the mean of diastolic blood pressure, there was a tendency to increase. Conclusion: During the hemodialysis process systolic blood pressure did not show a significant difference between the mean hours. In diastolic blood pressure, there was a significant difference between diastole 3 and diastole 4.